(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The motive of importance that has been given to renewable energy throughout the world, especially over the last five years, comes from a number of reasons. These reasons roughly point to the very rapid advancement of technology in all areas of life. The growing needs for energy sources are in function among other cases mentioned above or in the fast demographic growth of the world. In this paper, we discuss a practical case study on implementing an on-grid photovoltaic plant. The case study is considered in technical terms, and gives some discussion on the beneficial effects of using solar energy for the production of electric energy. A photovoltaic plant was implemented in the city of Elbasan, Albania based on preliminary simulations in terms of data such as geographical coordinates, solar radiation on the site in question and the nature of site’s relief where the plant was implemented. The results and discussion of the study in question consist in the technical quantitative presentation of the energy benefits provided by the photovoltaic plant and the economic impact in consumer and state level. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.